Biomass to biofuels : strategies for global industries - Vertès, Alain A. (Wiley, 2010)
"Biofuels are rapidly emerging as a popular solution to address global warming, rising energy costs and fuel supply shortages. However the environmental, economic and energetic benefits of biofuels still remain challenged. Amidst the global debate, Biomass to Biofuels: Strategies for Global Industries addresses these challenges through a discussion of the latest scientific advances in biofuel manufacturing. Combining scientific and business perspectives, the book provides a comprehensive overview of biofuel production technologies, highlighting both manufacturing and financial concerns inorder to define an appropriate R & D strategy." "This is a valuable handbook for scientists and policy makers working in the biofuels industry, as well as those working inthe related fields of petrochemicals and agriculture. It is also an important resource for students and academic researchers working on renewable energy solutions and bioprocessing technology."--Jacket.
Keywords: Biomass energy -- International cooperation.; Biomass energy industries -- International cooperation.; Globalization.; elektronické knihy; electronic books